Imaging DivIVA dynamics using photo-convertible and activatable fluorophores in Bacillus subtilis - Bach, Juri N.; Albrecht, Nadine; Bramkamp, Marc (Frontiers in Microbiology, 2014)
Most rod-shape model organisms such as Escherichia coli or Bacillus subtilis utilize two inhibitory systems for correct positioning of the cell division apparatus. While the nucleoid occlusion system acts in vicinity of the nucleoid, the Min system was thought to protect the cell poles from futile division leading to DNA-free miniature cells. The Min system is composed of an inhibitory protein, MinC, which acts at the level of the FtsZ ring formation. MinC is recruited to the membrane by MinD, a member of the MinD/ParA family of Walker-ATPases. Topological positioning of the MinCD complex depends on MinE in E. coli and MinJ/DivIVA in B. subtilis. While MinE drives an oscillation of MinCD in the E. coli cell with a time-dependent minimal concentration at midcell, the B. subtilis system was thought to be stably tethered to the cell poles by MinJ/DivIVA. Recent developments revealed that the Min system in B. subtilis mainly acts at the site of division, where it seems to prevent reinitiation of the division machinery. Thus, MinCD describe a dynamic behavior in B. subtilis. This is somewhat inconsistent with a stable localization of DivIVA at the cell poles. High resolution imaging of ongoing divisions show that DivIVA also enriches at the site of division. Here we analyze whether polar localized DivIVA is partially mobile and can contribute to septal DivIVA and vice versa. For this purpose we use fusions with green to red photoconvertible fluorophores, Dendra2 and photoactivatable PA-GFP. These techniques have proven very powerful to discriminate protein relocalization in vivo. Our results show that B. subtilis DivIVA is indeed dynamic and moves from the poles to the new septum.